The Influence of Organizational Commitment and Work–Life Balance on Organizational Sustainability with Communication Patterns as a Mediating Variable among Educational Staff at Universitas Muhammadiyah Surakarta - Farasyifa Mutiara Khansa; Irmawati Irmawati (Jurnal Economic Resource, 2026)
This study examines the effect of Organizational Commitment and Work–Life Balance on Organizational Sustainability, with Communication Patterns as a mediating variable among educational staff at Universitas Muhammadiyah Surakarta. A quantitative survey method was employed with 100 respondents, and the data were analyzed using PLS-SEM through SmartPLS. The results indicate that Organizational Commitment and Work–Life Balance do not have a direct effect on Organizational Sustainability. However, both variables have a positive and significant effect on Communication Patterns. Furthermore, Communication Patterns significantly influence Organizational Sustainability and effectively mediate the relationships between Organizational Commitment and Work–Life Balance with Organizational Sustainability. These findings highlight that organizational sustainability is not determined solely by employees’ commitment and work–life balance, but also largely depends on effective communication patterns within the organization. Open and effective communication is crucial to linking individual values to the organization’s long-term goals.